Twelve months effect of self-referral to inpatient treatment on patient activation, recovery, symptoms and functioning: A randomized controlled study. Issue 6 (June 2017) - Moljord, I.E.O.; Lara-Cabrera, M.L.; Salvesen, Ø.; Rise, M.B.; Bjørgen, D.; Antonsen, D.Ø.; Olsø, T.M.; Evensen, G.H.; Gudde, C.B; Linaker, O.M.; Steinsbekk, A.; Eriksen, L.
Highlights: The long term effect of SRIT showed no group differences in PAM, RAS and BASIS. No indication of adverse effects. SRIT can be recommended to increase patients own involvement in treatment. Abstract: Objective: To investigate the effect of having a contract for self-referral to inpatient treatment (SRIT) in patients with severe mental disorders. Methods: A randomized controlled trial with 53 adult patients; 26 participants received a SRIT contract, which they could use to refer themselves into a Community Mental Health Centre up to five days for each referral without contacting a doctor in advance. Outcomes were assessed after 12 months with the self-report questionnaires Patient Activation Measure (PAM-13), Recovery Assessment Scale (RAS), and the Behavior and Symptom Identification Scale (BASIS-32) and analyzed using linear mixed and regression models. Results: There was no significant effect on PAM-13 (estimated mean difference (emd) −0.41, 95% CI (CI):-7.49–6.67), nor on the RAS (emd 0.02, CI:-0.27–0.31) or BASIS-32 (0.09, CI:-0.28–0.45). An exploratory post hoc analysis showed effect of SRIT in those with low PAM below ≤47 ( p  = 0.049). Conclusion: There were no group differences after 12 months, but both groups maintained their baseline levels. Practice implications: SRIT contracts can be recommended as it supports the rights to self-determination, promote user participation in decision-making in own treatment without any indication of adverse effects.